THE CORRELATION BETWEEN THE INHERITED DEBT AND THE RIGHT OF OPTION ON SUCCESSION - Ana-Maria GHERGHINA (VASILE) (Challenges of the Knowledge Society)
A natural person’s patrimony consists, apart from rights (assets of the succession), of a liabilities side as well related to obligations that the patrimony’s holder bequeaths onto the heirs following his/her death. The succession implies that there are two parties, i.e. the assets of the succession and the inherited debt. The inherited debt is mainly made up of the inheritance duties and liabilities. The main components of the inherited debt are the debts the deceased has left, following that the duties shall be the obligations arising out after the succession will be opened. However, without defining the inherited debt concept in the specialized literature, successional liabilities have been considered to mean those patrimonial obligations of the deceased toward a third party or the inheritors existing in the successional patrimony on the opening of succession, regardless of their origin (contractual, tortious or legal). Inheritance duties refer to those obligations which did not exist in the de cujus patrimony, but come into existence devolving upon the heirs on the date of succession’s opening or subsequently after that time, either in consequence of the deceased’s desire, or independently of it. The main characteristic of the option on succession is that the right of option belongs exclusively to the presumptive heirs. From this point of view, the option on succession seems to have nothing in common with the inherited debt. Nevertheless, I intend to analyse the correlation between the two institutions from the perspective of the place inheritance creditors hold in the totality of rights of option. Their presence is only justified when there is an inherited debt.